Twelve-year clinical trajectories of multimorbidity in a population of older adults - Davide L. Vetrano; Albert Roso-Llorach; Sergio Fernández; Marina Guisado-Clavero; Concepción Violán; Graziano Onder; Laura Fratiglioni; Amaia Calderón-Larrañaga; Alessandra Marengoni (Nature Communications, 2020)
The co-occurrence of chronic diseases in the same person increases the risk of negative health events. Here authors show that grouping people based on their underlying disease patterns helps to identify homogeneous groups of people with similar needs and prognosis, facilitating personalized approaches.